The impact of servicescape dimensions towards customer satisfaction at theme restaurants in Melaka / Nurul Amirah Khalid - Khalid, Nurul Amirah (Faculty of Business and Management, 2018)
This study aims to examine the impact of servicescape dimensions towards customer satisfaction at theme restaurants in Melaka. The research is based on a sample of 150 respondents and the key objective to examine how ambient conditions, cleanliness and spatial layout and functionality influence customer satisfaction at theme restaurants. The results show that ambient conditions, cleanliness and spatial layout have significant influence towards customer satisfaction at theme restaurants. The most influential factor of servicescape dimensions towards customer satisfaction is spatial layout and functionality.